The discursive construction of teachers and implications for continuing professional development - Nair, Ramesh; Arshad, Roshayani (Universitas Pendidikan Indonesia, 2018)
The Malaysia Education Blueprint 2013-2025 is a document that spells out a plan of action for revamping the Malaysian education system. Therefore, it is no surprise that references are made to teachers and their role in ensuring the successful execution of the action plan. Although the blueprint does not set out a course of action for teachers of individual subjects, specific reference is made to English language teachers and this is ideologically significant. In order to understand this significance and how the blueprint positions Malaysian English language teachers, the document needs to be located within the wider discourse community, vis-Ã -vis through an intertextual reading. In this paper, we first examine the discursive construction of English language teachers in the blueprint as well as media texts to illustrate how these texts have collectively constructed the identity of Malaysian English language teachers. Next, we argue that this discursive construction of Malaysian English language teachers has had consequences for the way continuing professional development programmes have been organised for them in the first of three waves of the Malaysian Education Blueprint action plan from 2013 to 2015. The findings reveal that continuing professional development programmes during this period have focused predominantly on the training of the discursively constructed inept Malaysian English language teacher to ensure they possess the desired proficiency and are able to make changes to existing classroom practices that are aligned with the government agenda.